Clostridioides difficile Infection in Children: A 5-Year Multicenter Retrospective Study - Buonsenso, Danilo; Graffeo, Rosalia; Pata, Davide; Valentini, Piero; Palumbo, Carla; Masucci, Luca; Ruggiero, Antonio; Attinà, Giorgio; Onori, Manuela; Lancella, Laura; Lucignano, Barbara; Giuseppe, Martina Di; et al. (Frontiers in Pediatrics, 2022)
While there are numerous studies regarding Clostridioides difficile infection (CDI) in adults, literature on the pediatric population is scarce. Therefore, we performed a 5-year retrospective study between January 2014 and December 2018 in two referral centers in Rome, Italy. There were 359 patients tested for CDI who were enrolled: 87 resulted in positive and 272 in negative. CDI children had a higher number of previous-day hospital admissions (p = 0.024), hospitalizations (p = 0.001), and total hospital admissions (p = 0.008). Chronic comorbidities were more frequent in the CDI group (66.7% vs. 33.3%). Previous use of proton pump inhibitors and antibiotics was associated with CDI (p < 0.001). Among the antibiotics, only fluoroquinolones were significantly associated with CDI. Also, CDI children were more frequently exposed to antibiotics during the episode of hospitalization when children were tested. Our study provides an updated clinical and epidemiological analysis of children with CDI compared with a control group of children who tested negative. Further prospective studies could better define risk factors and preventive methods.